Effectiveness of biduri leaf extract (calotropis gigantea) as a denture cleanser in acrylic immersion against the growth of candida albicans: an experimental laboratory - Prasetyaningrum, Andania Ulfa Yuga; Astuti, Pudji; Gunadi, Achmad (Faculty of Dentistry Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: The high number of cases of tooth loss in Indonesia has led to the emergence of dentures. Dentures not appropriately kept clean can trigger cases of denture stomatitis due to Candida albicans. C. albicans is often detected on denture plates and causes denture stomatitis. Cleaning the dentures can prevent denture stomatitis, and chemical cleaning often uses synthetic materials such as alkaline peroxide. However, alkaline peroxide can cause side effects in the form of increased porosity on the surface of the acrylic plate, so an alternative natural ingredient, namely Biduri leaves (Calotropis gigantea), is needed because it has various active compounds such as alkaloids, flavonoids, phenols, saponins, terpenoids and tannins which have antifungal effects. This study aimed to determine the effective inhibitory power of Biduri leaf extract as a denture cleanser in acrylic immersion against the growth of C. albicans. Methods: Biduri leaves were extracted using the maceration method with 70% ethanol solvent to produce varying concentrations of 20, 30, 40, and 50%. The sample used in this research was an acrylic plate measuring 10x10x1 mm, soaked in artificial sterile saliva for 1 hour, then soaked in each sample group for 8 hours, after that it was placed in 10 ml of Sabouraud Dextrose Broth (SDB) media, and vibrated for 30 seconds using a mixing vortex, spreading 0,1ml SDB on Saboraud Dextrose Agar (SDA) and incubated for 48 hours. The growth of C. albicans was observed and counted using the colony counting method. Results: This research showed an inhibitory power of Biduri leaf extract in concentrations of 20, 30, 40, and 50% on the growth of C. albicans, with a concentration of 50%, having the most significant inhibitory power. Conclusion: Biduri leaf extract as a denture cleanser has an inhibitory power on the growth of C. albicans.KEYWORDS Biduri leaves, Calotropis gigantea, heat cured acrylic, Candida albicans